Are multidisciplinary consultation meetings for prenatal diagnosis achievable in a low-income country? A descriptive cross-sectional survey in Benin - Antoine Séraphin Gbenou; Jean-François Lecompte; Jean Bréaud; Monsoia Gildas Yassegoungbe; Beaudelaire Romulus Assan; Amoussou Sedjro Clotaire Romeo Houegban; Codjo Serge Metchihoungbe; Christine Tschabu Aguemon; Sidoine Bitho Gbetey (BMJ Publishing Group, 2023)
Objective The multidisciplinary antenatal diagnosis staff bring together practitioners who are involved in the management of the antenatal period at birth. This project was designed following the French experience to institute multidisciplinary consultation meetings for prenatal diagnosis (MCMPD) in Benin.Methods This is a descriptive cross-sectional study examining the knowledge, attitudes, and practices of Beninese practitioners in the field of MCMPD to develop the pilot phase of the project.Results We collected 108 participants from different specialties. Pediatricians and pediatric surgeons were in the majority at 23.9% and 16.5%, respectively. Sixty-seven percent of participants were from the public sector (n=75). One practitioner felt that it was not a good idea to implement these meetings. Almost all staff (96.2%) agreed that this meeting would have a positive impact on reducing neonatal mortality. Omphalocele (58.5%), spina bifida aperta (43.6%), and gastroschisis (34%) were the most commonly diagnosed antenatal conditions in Benin. No neonatal pathology required medical termination of the pregnancy according to 35.6% of the participants.Conclusions The objective of reducing infant mortality due to medical and surgical pathologies is a noble one and deserves to be supported. This innovative project, developed through this study, the first of its kind in the subregion, will contribute inexorably to the achievement of the third Goal Sustainable Development.